2022
DOI: 10.1590/1516-3180.2020.0718.r1.18052021
|View full text |Cite
|
Sign up to set email alerts
|

Recent dengue virus infection: epidemiological survey on risk factors associated with infection in a medium-sized city in Mato Grosso

Abstract: BACKGROUND: Dengue is considered to be the most important arbovirus worldwide, with important complications that increase its lethality. In Brazil, an endemic country, the disease reaches significant incidence levels, with occurrences of serious cases and high costs of hospitalizations for its treatment. OBJECTIVE: To analyze risk factors among individuals with recent histories of dengue infection in a medium-sized city in Mato Grosso. DESIGN AND SETTING: Descriptive cross-sectional study, of epidemiological-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…MacCormak-Gelles [80], when analyzing the epidemiological and determining characteristics of dengue transmission in Fortaleza (Brazil), inferred a strong association with poverty and irregular retrieval of solid waste during low-transmission periods. That way, in the literature, several other authors [52,56,57,61,73,91,94,97,98] corroborate the question of where socioeconomic and/or demographic variables, sometimes allied to environmental factors, interfere for smaller or greater incidences of vector-transmitted diseases.…”
Section: Integrativementioning
confidence: 76%
See 1 more Smart Citation
“…MacCormak-Gelles [80], when analyzing the epidemiological and determining characteristics of dengue transmission in Fortaleza (Brazil), inferred a strong association with poverty and irregular retrieval of solid waste during low-transmission periods. That way, in the literature, several other authors [52,56,57,61,73,91,94,97,98] corroborate the question of where socioeconomic and/or demographic variables, sometimes allied to environmental factors, interfere for smaller or greater incidences of vector-transmitted diseases.…”
Section: Integrativementioning
confidence: 76%
“…In addition, precarious access to water for potability purposes encourages the population to adhere to alternative water sources (generally, individual/private wells), which was observed in 14% (3/22) of the studies [57,69,98] in regions of America and Asia, whose modality favored the increased risk of disease incidence (p < 0.001).…”
Section: Significant Relationship Between Water and Aedes Breeding Sitesmentioning
confidence: 99%
“…There is a lack of innovation to address these endemic diseases, and there is a need for improvement in the training of health professionals, elimination of breeding sites, and health education initiatives for the general population. A study conducted in Icaraí-Caucaia (state of Ceará) on health education for dengue prevention and control concluded that health education initiatives were conducted ineffectively, without dialogue between health professionals and the general public 49 . Therefore, knowledge about these arboviruses and the ways to manage infections with them must be spread to remote communities, which do not know much about these pathogens, so that the population knows how to recognize the signs and symptoms of any complications that may occur and seek appropriate medical assistance.…”
Section: Discussionmentioning
confidence: 99%
“…Diante disso, foi realizada uma análise comparativa entre os anos supracitados, no qual foi possível verificar um aumento expressivo de novos focos no município de Caçador, se tornando um dado preocupante para a incidência de possíveis casos, reforçando ainda mais a importância do presente trabalho. Groskopf (2021), demostrou em seu estudo, realizado no período de 2016 a 2020 no estado de Santa Catarina, que na maior parte do período vem ocorrendo um aumento crescente tanto nas notificações e casos confirmados de dengue, quanto na quantidade de focos detectados. Resalta que após o anos de 2016, no qual hou um grande numero de casos no estado, as ações de vigilância entomológica do Aedes aegypti foram intensamente otimizadas, refletindo qem um queda importante nos anos subssequentes, de 2017 e 2018.…”
Section: Metodologiaunclassified